2022
DOI: 10.1177/09567976211073135
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Belonging Predicts Depressive Symptomatology in College Students

Abstract: Feeling a sense of belonging is a central human motivation that has consequences for mental health and well-being, yet surprisingly little research has examined how belonging shapes mental health among young adults. In three data sets from two universities (exploratory study: N = 157; Confirmatory Study 1: N = 121; Confirmatory Study 2: n = 188 in winter term, n = 172 in spring term), we found that lower levels of daily-assessed feelings of belonging early and across the academic term predicted higher depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 55 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Partial mediation model showed that on one hand, life stressors can directly induce depressive episodes, stimulation frustration and multiple loading were the main stressors for vocational students. Long-term frustration in studies, improper management of interpersonal relationship and increasing employment pressure cause heavy psychological burden on students, who can not find a sense of belonging, with a result of depression [ 36 ]. On the other hand, life stressors can induce depressive episodes through stress response [ 37 ], which further verifies the diathesis-stress theory of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Partial mediation model showed that on one hand, life stressors can directly induce depressive episodes, stimulation frustration and multiple loading were the main stressors for vocational students. Long-term frustration in studies, improper management of interpersonal relationship and increasing employment pressure cause heavy psychological burden on students, who can not find a sense of belonging, with a result of depression [ 36 ]. On the other hand, life stressors can induce depressive episodes through stress response [ 37 ], which further verifies the diathesis-stress theory of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Belonging has been theorized that it must be satisfied first before achieving other higherorder needs (e.g., self-actualization;Staryhorn, 2018). For college students in particular, feelings of belonging are linked to less depressive symptoms (Dutcher et al, 2022), greater sense of meaning in life (Lambert et al, 2013;Zhang et al, 2018), life satisfaction (OECD, 2017), and better emotional well-being (see Allen et al, 2018 for review).…”
Section: Benefits Of Belongingmentioning
confidence: 99%
“…The few studies examining first year college student experiences focus primarily on belonging, safety, homesickness, and academic stress. Students feeling less belonging ( Dutcher et al, 2022 , Gopalan and Brady, 2020 ), unsafe ( Maffini, 2018 ), homesick ( Thurber & Walton, 2012 ), or academic stress ( Newcomb-Anjo et al, 2017 ) may report more depression, anxiety, or perceived stress. Those feeling less belonging or more homesickness are less likely to finish college ( O’Keeffe, 2013 , Thurber and Walton, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Social support may mitigate these risks by helping students cope with academic stress ( Dwyer & Cummings, 2001 ). Greater belonging is associated with retention, better mental health, and use of campus services ( Dutcher et al, 2022 ), but may be related to greater binge drinking ( Berger et al, 2022 ). According to the transition catalyst model, risk-taking and substance use may be factors in the developmental transition in young adulthood, where the role of alcohol potentially facilitates socializing and making new friends when entering new environments ( Schulenberg & Maggs, 2002 ).…”
Section: Introductionmentioning
confidence: 99%